2013
DOI: 10.1038/nrneph.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy improves blood pressure control and reduces vascular risk in CKD

Abstract: In patients with chronic kidney disease (CKD), the prevalence of increased blood pressure during sleep and blunted sleep-time-relative blood pressure decline (a nondipper pattern) is very high and increases substantially with disease severity. Elevated blood pressure during sleep is the major criterion for the diagnoses of hypertension and inadequate therapeutic ambulatory blood pressure control in these patients. Substantial, clinically meaningful ingestion-time-dependent differences in the safety, efficacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 117 publications
(280 reference statements)
0
40
0
Order By: Relevance
“…The aim of chronotherapy is to administer medicines at certain times of the day to maximize efficacy and reduce side effects. Many hypertension medications are usually taken in the morning, however convincing evidence concerning the effects of chronotherapy shows the benefit of taking at least one hypertension medication at night (for an excellent review, see (Hermida et al 2013)). The MAPEC study followed over 2000 hypertensive patients over the course of a median of 5.6 years (Hermida et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of chronotherapy is to administer medicines at certain times of the day to maximize efficacy and reduce side effects. Many hypertension medications are usually taken in the morning, however convincing evidence concerning the effects of chronotherapy shows the benefit of taking at least one hypertension medication at night (for an excellent review, see (Hermida et al 2013)). The MAPEC study followed over 2000 hypertensive patients over the course of a median of 5.6 years (Hermida et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of blood pressure lowering drugs at bedtime could therefore lead to significant improvement is this clinical setting. 80,86 …”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…In mammals, mounting evidence has demonstrated that the circadian clock regulates a multitude of physiological functions including but not limited to: metabolism, immune response, renal function, sleep-wake cycles, and blood pressure [3, 4]. Interestingly, it has been shown that deregulation of the circadian clock can also be attributed to certain pathological states, including hypertension [5]. The purpose of this review is to examine the role of the circadian clock genes in the regulation of blood pressure and their potential role in hypertension from insights gathered through the use of rodent models.…”
Section: Introductionmentioning
confidence: 99%